Kesulitan Siswa Memahami Pereaksi Pembatas Di SMA Kabupaten Barito Utara Dan Kota Palangka Raya Tahun Pelajaran 2015/ 2016 - Siti Hayati; Suandi Sidauruk; Abudarin (Jurnal Ilmiah Kanderang Tingang, 2018)
This study aims to identify and explain the difficulties of students in understanding the concept of limiting reagent, including: determining the limiting reagent, if all reagents are in the form of elements and gas molecules; if draw all the reagents in gas molecules; if the moles of each reactant are known; and if the mass of each reactant is known. The population of the study was students of class XI IPA SMA Negeri in North Barito Regency and Palangka Raya City with a research sample of 367. Students' difficulties were examined by using the limiting reagent concept understanding test instrument accompanied by interviews to explore the difficulties experienced by students. The test instrument has four answer choices and four reasons. Content validity was tested by four experts. The average difficulty level is 0.42 and the difference is 0.49. Test reliability was calculated using Cronbach's Alpha. The results showed that students had difficulty understanding the concept of limiting reagent in terms of the macroscopic level an average of 67.24% students and the microscopic level an average of 49.33% students. This means that the macroscopic level of difficulty is higher than the microscopic level of difficulty. The difficulty at the macroscopic level identified is that students have difficulty in converting volume, mass into units of moles. The identified difficulty at the microscopic level is that students have difficulty in understanding so that in solving questions students tend to choose the right answer but wrong in choosing the reason.